Evaluation of the Impact of IKN Development on Increasing Tourism Sector Competitiveness, Increasing Tourist Income, and Increasing the Number of Tourism Visits: A Case Study on Tourist Destinations in East Kalimantan - Zulfikri, Agung; Ishak, Riani Prihatini; Judijanto, Loso (West Science Journal Economic and Entrepreneurship, 2023)
This research investigates the impact of Information and Knowledge Networks (IKN) development on the tourism sector in East Kalimantan through a quantitative analysis. A sample of 150 participants, comprising tourists, local businesses, and stakeholders, provided insights into the relationships between IKN development and Increasing Tourism Sector Competitiveness, Increasing Tourist Income, and Increasing the Number of Tourism Visits. The study employed Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to analyze the data. The measurement model assessment confirmed the reliability and validity of the constructs, while the structural model analysis revealed significant positive relationships between IKN development and the dependent variables. The overall model fit was assessed using various indices, and hypothesis testing supported the significance of the paths. The R-Square values indicated that the model effectively explains a substantial proportion of the variability in tourism outcomes. The findings contribute to the understanding of the role of IKN in shaping the tourism sector and offer practical implications for stakeholders in East Kalimantan.